Consciousness of training body part(s) by showing a picture of various exercises in trunk muscles - Oshita, K.; Matsuzaki, T.; Hikita, A.; Miyazaki, R.; Hagiwara, G.; Tashiro, T.; Tsuno, T.; Higuchi, Y.; Funatsu, K. (International Journal of Sport & Health Science, 2019)
The aim of the present study was to investigate the consciousness among young people (n = 1000) of training body part(s) by showing participants a picture of trunk muscle exercises through a questionnaire-based survey. The participants were shown a picture of bent-knee sit-up (sit-up), back extension (back-EXT), and plank from elbows to toes (plank), and were asked which body part(s) they felt was being trained in each picture. As for the frequency of performing these exercises, only 3% and 8% of all the participants had never performed sit-up and plank exercises, respectively. On seeing the picture, 40-60% of the participants who had no experience doing a sit-up or back-EXT felt that these exercises were to train not only the agonist muscle but also the antagonist muscle. Approximately 40% of the participants who had no experience doing a plank exercise felt that it was not to train the epigastrium or hypogastrium area. Among the participants who experienced doing a plank exercise without a previous experience of strength training under professional supervision, more than half felt that plank exercise was appropriate to train not only the trunk but also the upper limb or lower leg. Furthermore, among the participants who had a previous experience of strength training under professional supervision, approximately 30% had such an opinion. Therefore, although the penetration rate of these trunk exercises are high, doing trunk exercises by referring to only a picture may result in the participants not properly understanding how the body part(s) should be trained during the exercise. Therefore, to enhance the benefits of trunk exercises, individuals (even those who had a previous experience of training under professional supervision) always need to be instructed through appropriate supervision on the correct technique and knowledge about the exercises.